ChemInform Abstract: Current Trends and Future Prospects of Lipstatin: A Lipase Inhibitor and Pro‐Drug for Obesity. Issue 50 (December 2015) - Kumar, Punit; Dubey, Kashyap Kumar
Abstract: Review: 152 refs.